Audiovisual Translation and Language Teaching: A Proposal on How to Use Respeaking to Improve Oral Skills - Belenguer Cortés, Luz (Journal of Audiovisual Translation, 2024)
Audiovisual Translation (AVT) and foreign language (FL) learning have converged in recent decades to be an effective combination to improve language skills. Respeaking is one of the few modalities that involves oral practice, since it combines shadowing – a technique involving the immediate and simultaneous repetition of spoken language by a language learner, typically with a brief delay behind the speaker – and the subtitling practice. The present paper aims to offer a proposal on the use of respeaking in FL acquisition emphasising its advantages for FL speaking skills. First, the article will explore the current landscape of language learning and Didactic Audiovisual Translation (DAT). It will then define the concept of respeaking and examine the challenges associated with this AVT method. Subsequently, the discussion will focus on the technique of shadowing, its link to respeaking and its potential benefits for improving oral skills. Finally, the concept of didactic respeaking will be introduced. A proposal will be provided to determine what didactic materials should be used as such, and some reflections on how respeaking can be assessed in FL teaching will be made. The final conclusions reflect on the feasibility of introducing respeaking as a didactic tool in FL teaching, which could be a potential new trend in DAT. Lay summary Audiovisual translation, or the translation of audiovisual texts such as film using modes such as subtitling and dubbing, has been used in language teaching over the years to help students improve their language skills. When studying, learners still struggle when it comes to speaking in class, and they find this ability is the hardest to learn. In audiovisual translation, there is a modality called “respeaking” that involves speaking and listening at the same time. In respeaking, respeakers listen to an oral message and they repeat it so a voice-recognition software can transcribe it. This is frequently used to create live subtitles for people who are deaf or hard of hearing so they can enjoy the programme or the event despite their hearing impairment. This enables them to understand dialogues or sounds because subtitles reflect what is going on and respeakers adapt the information to their needs. If we refer to how respeakers do their job, we can say that respeaking is one of the few modalities of audiovisual translation that involves speaking. We say this because when respeakers respeak, they do what we call “shadowing”: this means that respeakers repeat the message they are hearing out loud, so we can say they are the shadow of the original message. To do so, we will first explain what has been done in audiovisual translation and language teaching until today. Then, we will focus on respeaking, so we will define what it is and the limitations we can find in it. Here we will also talk about shadowing, and how it has been proved that it helps students to improve their speaking. After this, we will show a proposal on how to use repeaking in a lesson plan, showing the materials, the exercises and the tasks that can be done in a foreign language class, and we will wrap up the article by thinking of the applications of respeaking in language teaching and how this could be use from now on to teach languages.